2014
DOI: 10.9734/ijpss/2014/11421
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Days to Flowering on Plant Height and Yield of Rice (Oryza sativa L.)

Abstract: Aims:To study effect of days to flowering on the plant height and yield of rice. Study Design: Experiment was carried out according to the complete randomized block design. Four replications were designed for the experiment and each replicate consisted of 3 lines and twenty plants were included in to each line. Data were collected in 80 plants of the each middle line of four replicates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…[18] reported that days to flowering was controlled by both genetic and environmental factors. Ranawake et al [19] concluded that days to flowering and plant height was positively correlated.…”
Section: Total Number Of Tillers/hillmentioning
confidence: 99%
“…[18] reported that days to flowering was controlled by both genetic and environmental factors. Ranawake et al [19] concluded that days to flowering and plant height was positively correlated.…”
Section: Total Number Of Tillers/hillmentioning
confidence: 99%
“…Days to owering and maturity Flowering refers to opening and closing of oret followed by panicle exertion and heading (Slaton 2011). Days to 50% owering and days to maturity represents the time period taken by plants from sowing to maturity (Ranawake et al 2014). Of the 117 boro rice cultivars studied, V1 Nagaon took the highest days to 50% owering (132 days) and maturity (296 days) whereas Luit took the lowest days to owering (57 days) and maturity (153 days) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1). Luit cultivar thereby, may be considered a better cultivar in terms of days to maturity as, rice plants with minimum days to owering and maturity indicates to be a better cultivar (Ranawake et al 2014). As per IRRI, rice cultivars within the range 105-120 days to maturity are termed to be short duration cultivars and beyond 150 days as long duration cultivars (IRRI 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adaptation of rice to different agroclimatologically zones such as temperature fluctuation, light day intensity, and short day condition results in variation in days to flowering. Ranawake et al (2014) reported that the effect of days to flowering to the rice yield is positively correlated and maximum started from 80 days up to 90 days and becomes negative when exceeding 90 days. Another explanation to this phenomenon is the fact that higher sinking productivity was exhibited by a higher score in filled grain percentage of those that start flowering earlier compared to late flowering, which reduced the dry matter accumulation in grain.…”
Section: Discussionmentioning
confidence: 99%